Christian Religious Education Teaching Syllabus : St Luke's Gospel and its relevance to Africa today ; Uganda Certificate of Education ; senior 1- 4 - Uganda Government (Kampala : Natiobnal Curriculum Development Centre, 2008)
St. Luke's Gospel and its Relevance to Africa
Includes bibliographical references (p. 125).
Keywords: Christian Religious Education -- Syllabus -- Uganda